Pengaruh Core Stability Terhadap Fleksibilitas Lumbal Petugas Kesehatan RSUD KANJURUHAN Kabupaten Malang - Dimas Setyawan; Achmad Fariz; Retno Dewi Prisusanti; Agung Hadi Endaryanto (Jurnal Keperawatan Muhammadiyah, 2022)
Objective:. Lumbar flexibility is the maximum ability of the lumbar muscles which is important to maintain because it is closely related to the functional ability of the body in carrying out daily activities. This study aims to analyze the effect of core stability exercise on lumbar flexibility in Kanjuruhan Hospital employees.Methods: The independent variable of this study was  core stability exercise, and the dependent variable was the lumbar flexibility. There were 25 subjects in this study using purposive sampling technique. The design of this study used pre expemerimtal one group pretest and posttest design.Results:  The results of this study are p-value = 0.000 (p <0.05) meaning that there is an effect of core stability exercise on the lumbar flexibility of employees at Kanjuruhan Hospital, Malang Regency.Conclusion: Lumbar flexibility before core stability exercise mean ± SD = 29.56 ± 3.163, after core stability exercise mean ± SD = 32.44 ± 4.302. There is an effect of core stability exercise on lumbar flexibility of employees at Kanjuruhan Hospital, Malang district (p value = 0.000).